2015
DOI: 10.4155/fso.15.55
|View full text |Cite
|
Sign up to set email alerts
|

Importance of Measuring Testosterone in Enzyme-Inhibited Plasma for Oral Testosterone Undecanoate Androgen Replacement Therapy Clinical Trials

Abstract: Aim:Testosterone undecanoate (TU) is metabolized by nonspecific esterases in blood to testosterone (T). Typical clinical practice has been to analyze testosterone in human serum. The degradation of TU to testosterone was evaluated in conditions typically used in clinical studies.Methods & Results:Freshly collected whole blood was fortified with TU at known concentration. Serum was prepared and T concentration was determined by LC–MS/MS. It was observed that TU degrades extensively to T in human blood under con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 10 publications
0
20
0
Order By: Relevance
“…We previously demonstrated that non‐specific esterases in blood cells can convert the T ester, T enanthate, to T in blood and may affect the accuracy of the measured T concentration (Wang et al ., ). When TU added to blood was allowed to stand at RT, the T concentration measured in the serum was higher than the initial T concentration (Lachance et al ., ). The results of our earlier study showing that TU added to blood had little effect on T measurements were erroneous and were probably due to the insolubility of TU in aqueous solutions (Wang et al ., , ; Lachance et al ., ).…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…We previously demonstrated that non‐specific esterases in blood cells can convert the T ester, T enanthate, to T in blood and may affect the accuracy of the measured T concentration (Wang et al ., ). When TU added to blood was allowed to stand at RT, the T concentration measured in the serum was higher than the initial T concentration (Lachance et al ., ). The results of our earlier study showing that TU added to blood had little effect on T measurements were erroneous and were probably due to the insolubility of TU in aqueous solutions (Wang et al ., , ; Lachance et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…When TU added to blood was allowed to stand at RT, the T concentration measured in the serum was higher than the initial T concentration (Lachance et al ., ). The results of our earlier study showing that TU added to blood had little effect on T measurements were erroneous and were probably due to the insolubility of TU in aqueous solutions (Wang et al ., , ; Lachance et al ., ). All our ex vivo spiking experiments showed significant concentration‐dependent ester hydrolysis when steroid esters (TU and DMAU) were added to the blood, resulting in increased measured T or DMA.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations